2018
DOI: 10.1029/2017wr021749
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Landscape Characteristics on Groundwater Dissolved Organic Nitrogen: Insights From Machine Learning Methods and Sensitivity Analysis

Abstract: The effect of groundwater nutrient inputs on river and estuary water quality and the potential impacts of urbanization on groundwater are central concerns in many coastal areas. It has been previously identified that dissolved organic nitrogen (DON) can be the dominant form of total dissolved nitrogen (TDN) in some aquifers. However, there is a paucity of evidence about the sources and flow paths of DON, relative to inorganic nitrogen in groundwater. DON and dissolved organic carbon/DON were first compared aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Classification and regression trees (CARTs, [56]) are methods to partition the variable space based on a set of rules embedded in a decision tree (see Figure 1 below), where each node splits according to a decision rule; see e.g., Hastie et al [58] (pp. [305][306][307][308][309][310][311][312][313][314][315][316][317], and the review in Loh [19]. In this way, the variable space is partitioned into a set of rectangles, and a model is fitted to each set, which in the simplest case can be a constant.…”
Section: Classification and Regression Treesmentioning
confidence: 99%
“…Classification and regression trees (CARTs, [56]) are methods to partition the variable space based on a set of rules embedded in a decision tree (see Figure 1 below), where each node splits according to a decision rule; see e.g., Hastie et al [58] (pp. [305][306][307][308][309][310][311][312][313][314][315][316][317], and the review in Loh [19]. In this way, the variable space is partitioned into a set of rectangles, and a model is fitted to each set, which in the simplest case can be a constant.…”
Section: Classification and Regression Treesmentioning
confidence: 99%
“…Nidzgorski and Hobbie (2016) found similar benefits for soil phosphate and studied implications for groundwater quality using hydrological modeling. Nitrogen impacts were inconsistent, seemingly differing between years due to climate variability (Nidzgorski & Hobbie, 2016), although Wang et al (2018) identified some evidence of urban forest benefits for groundwater dissolved organic nitrogen. Whilst Decina et al (2018) studied nutrients in throughfall and soil solution for individual trees, they did not report soil concentrations under contrasting landcover, so data were not included in meta-analysis.…”
Section: Plot-scale Findingsmentioning
confidence: 99%
“…The probability with which data points are selected for the next training set is not constant and equal for all data points. The selection probability increases for data points that have been misestimated in the previous iteration; data points that are difficult to classify would receive higher selection probabilities than easily classified data points (Yang et al, 2010;Erdal and Karakurt, 2013). For RF and GBM, the most commonly used base learner is a classification and regression tree (CART).…”
Section: Random Forest and Gradient Boosting Machinesmentioning
confidence: 99%
“…Meanwhile, data-driven machine learning (ML) methods are increasingly being applied to quantify relationships between soil, water and environmental landscape attributes (Lintern et al, 2018;Wang et al, 2018;Guo et al, 2019). For instance, random forest (RF), a widely used ML method, was used to model the spatial and seasonal variability of nitrate concentrations in streams (Álvarez-Cabria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%